Analysis of the effects of the plant growth promoting substances GR24 and smoke water on abiotically stressed Nicotiana benthamiana seedlings - Steenkamp, Letitia Elizabeth (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2012.